2015
DOI: 10.1371/journal.pbio.1002132
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Cell Stress Response of Plasmodium falciparum to Overcome Artemisinin Resistance

Abstract: Successful control of falciparum malaria depends greatly on treatment with artemisinin combination therapies. Thus, reports that resistance to artemisinins (ARTs) has emerged, and that the prevalence of this resistance is increasing, are alarming. ART resistance has recently been linked to mutations in the K13 propeller protein. We undertook a detailed kinetic analysis of the drug responses of K13 wild-type and mutant isolates of Plasmodium falciparum sourced from a region in Cambodia (Pailin). We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
415
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(444 citation statements)
references
References 62 publications
27
415
0
2
Order By: Relevance
“…Other studies suggest that drug treatment is also able to slow or halt (dormancy) the life cycle of P. falciparum parasites, which is thought to be a parasite stress response allowing parasites to survive treatment (33)(34)(35)(36)(37). Hence, it seems likely that slower maturation occurs as a parasite survival mechanism in response to environmental stress, perhaps as a result of the parasite directing resources to mitigate damage caused by some form of stress placed on the parasite, whether by drug or by the host environment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that drug treatment is also able to slow or halt (dormancy) the life cycle of P. falciparum parasites, which is thought to be a parasite stress response allowing parasites to survive treatment (33)(34)(35)(36)(37). Hence, it seems likely that slower maturation occurs as a parasite survival mechanism in response to environmental stress, perhaps as a result of the parasite directing resources to mitigate damage caused by some form of stress placed on the parasite, whether by drug or by the host environment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that this mechanism of resistance to vancomycin involves the permanent activation of a stress response in resistant bacteria [84]. A recent study revealed that malaria parasites resistant to artemisinin exhibit an enhanced cell stress response with lower levels of ubiquitinated proteins and delayed onset of cell death compared to artemisinin susceptible parasites, suggesting the involvement of a proteasomeengaging cell stress response [85]. Clinically used proteasome inhibitors strongly synergize artemisinin activity against both sensitive and resistant parasites.…”
Section: Targeting Stress Responsesmentioning
confidence: 95%
“…More recently, a mutation on the K13-Propeller locus has been observed to be associated to DPC in Cambodia [9]; subsequently, additional mutations on the same gene have been observed in other regions in South Asia [10][11][12][13][14][15][16]. This promising marker is currently used in association with DPC to identify ART resistance but both still require a substantial clinical validation.…”
Section: Markers Of Artemisinin Resistancementioning
confidence: 99%
“…This promising marker is currently used in association with DPC to identify ART resistance but both still require a substantial clinical validation. Wide clinical trials to correlate DPC and K13 mutations with confirmed ART resistance are therefore needed to assess the isolated and cumulative performances of the markers [16]. Unfortunately the intrinsic complexity of those markers do not favor the sustainability and the implementation of the large clinical trials that should be required to validate and to assign precise performances to available makers.…”
Section: Markers Of Artemisinin Resistancementioning
confidence: 99%
See 1 more Smart Citation